Supply constraints and waitlists in new product diffusion. (14th April 2018) - Keith, David R.; Sterman, John D.; Struben, Jeroen
Abstract: Constraints on production capacity adjustment present a strategic and operational problem for managers launching products when demand is uncertain. Stock‐outs can be costly if demand exceeds available product supply, as sales are deferred or lost when prospective customers are waitlisted. Recent research on diffusion under supply constraints has analyzed launch strategies to minimize the chance of stock‐outs. Others suggest that waitlisted buyers generate social exposure that can boost customer demand and shape the diffusion process. We develop a generalized model of new product diffusion under supply constraints that explicitly accounts for endogenous customer waitlisting and waitlist‐generated word‐of‐mouth. We estimate the model for a prominent example of waitlisting, the launch of the Toyota Prius hybrid‐electric vehicle in the U.S.A., finding evidence of positive word‐of‐mouth from waitlisted buyers. Inclusion of endogenous supply constraints and waitlisting also alters the estimated contribution of marketing and adopter word‐of‐mouth. Copyright © 2018 System Dynamics Society